Employment of foreigners from outside the European Union through temporary employment agencies - Szypniewski, Michał (Temporary employment as an atypical form of employment: No. 19/2022, 2022)
The aim of the foregoing study is to indicate the interdependence between the law on the employment of foreigners and the law on the employment of temporary workers. First, the author analyzes the assumptions of the law on the employment of foreigners. Next, he discusses the assumptions of the law on the employment of temporary workers, which makes it possible to crystallize mutual relations and connections. The author contrasts dogmatic-legal analysis with axiological conditions and tries to explain the classic conflict between the protection of the employee’s interest and the protection of the domestic labour market.